Excited state intramolecular proton transfer mechanism of o-hydroxynaphthyl phenanthroimidazole - 刘爽;马艳珍;杨云帆;刘松松;李永庆;宋玉志 (Chinese physics B, 2018)
By utilizing the density functional theory （DFT） and the time-dependent density functional theory （TDDFT）, the excited state intramolecular proton transfer （ESIPT） mechanism of o-hydroxynaphthyl phenanthroimidazole （HNPI） is studied in detail. Upon photo is excited, the intramolecular hydrogen bond is obviously enhanced in the Sl state, which thus promotes the ESIPT process. Hydrogen bond is shown to be strengthened via comparing the molecular structures and the infrared vibration spectra of the So and S1 states. Through analyzing the frontier molecular orbitals, we can conclude that the excitation is a type of the intramolecular charge transfer excitation, which also indicates the trend of proton transfer in SI state. The vertical excitation based on TDDFT calculation can effectively repeat the absorption and fluorescence spectra of the experiment. However, the fluorescence spectrum of normal structure, which is similar to the spectrum of isomer structure is not detected in the experiment. It can be concluded that the fluorescence measured in the experiment is attributed to both structures. In addition, by analyzing the potential energy curves （PECs） calculated by the B3LYP functional method, it can be derived that since the molecule to cross the potential barrier in the S 1 state is smaller than in the So state and the reverse proton transfer process in the $1 state is more difficult than in the So state, the ESIPT occurs in the S1 state.